The Concept of the Role of Parents in the Application of Morality to Children (Study of Surah Luqman Verses 12-19 in Tafsir Al-Misbah) - Savira, Varadiba; Drajat, Amroeni (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Education is a process that humanizes humans. This concept shows that without strong morality, education will not be achieved. This article aims to analyze Surah Luqman verses 12-19, which contain important themes in moral education for children. This study uses a qualitative method with a literature study approach, relying on the interpretation text